(untitled) (Eurasian Research Bulletin, 2022)
The article is devoted to the peculiarities of the organization of independent work at the university. It attempts to include each student in the process of independent activity, taking into account individual characteristics, to teach how to plan educational work, to make the transition from simple knowledge to more complex ones.